TELAAH KESYARI’AHAN ZAKAT BURUNG WALET DI KECAMATAN DUA BOCCOE KABUPATEN GOWA - Bahrul Ulum Rusydi; Rahmawati Muin; Abdul Wahab; Nur Adriana (Al-Amwal : Journal of Islamic Economic Law, 2020)
This study aims to examine the syariah of swallow zakat implementation in Dua Boccoe District, Bone Regency. To answer this, the research design used is qualitative research with a normative and sociological approach. The results of the study found that the implementation of zakat on swallow birds in the research location was not fully in accordance with the rules and regulations in Islam. This is because most of the swallow entrepreneurs pay zakat in different ways and use their own rules, some even do not pay zakat at all.